The Effect of Profitability on Dividend Policy in Indonesian State-Owned Banks - Herningsih Sutri Lembong (AIBPM Publisher, 2020)
This study is conducted to determine the effect of the profitability variable on dividend policy in Indonesian state-owned banks. The method used in this research is quantitative method using numerical data which are tested using panel data regression analysis. The population of this study is PT Bank Rakyat Indonesia (Persero) Tbk, PT Bank Negara Indonesia (Persero) Tbk, PT Bank Tabungan Negara (Persero) Tbk, and PT Bank Mandiri (Persero) Tbk, where the data samples are the financial statements for fiscal year 2011 through fiscal year 2019. The study result is the NPM (profitability) regression coefficient of -0.731653. This value indicates the negative direction on dividend policy. Moreover, the results of t-test obtain a significant level of 0.0409 which is smaller than 0.05 (level of significance). From these results, it can be concluded that profitability which is measured using net profit margin (NPM) has a negative but significant effect on dividend policy (DPR). This means that value of profitability which is measured by the net profit margin (NPM) is not the basis for the number of dividends that will be distributed by the company management to the shareholders.